فنّ الخطّ العربي بين الروح الإسلامية والبعد الاستيتيقي - Khadidja Merat (Journal of Calligraphy, 2021)
This research tries to explain the art of Arabic calligraphy; This ancient art, with its distinctive formations, decorations, and geometries, decorated with Islamic letters of the spirit, imparts a special breath to the fonts and gives them an aesthetic imprint and medallion of difference and individuality. Therefore, this intervention falls under the Title “ Arabic Calligraphy Art Between the Islamic Spirit and the Strategic Dimension”, is an attempt to answer the central problem of calligraphy, namely: Arabic combining the Islamic spirit with an aesthetic dimension? Or in other words, how does the spirit of Islam give Arabic calligraphy an aesthetic and aesthetic dimension? This study will rely on a historical descriptive approach, because it will describe the phenomenon of Arabic calligraphy art in addition to its history, origin, and development, to achieve the focus and axis of the study which is represented in the aesthetics and reliability of the work. this calligraphy. The study achieved a series of results, the most important of which were: 1- Arabic calligraphy is a symbol of Arab civilization. 2- The emergence of Islam contributed to the interest in calligraphy and the transition from the spoken system to the written system. 3 - Muslims are attracted to Arabic calligraphy as a means to communicate with them, communicate their civilization and culture, and spread their religion throughout the world. 4 There is a close connection between Arabic calligraphy and Arabic identity, namely that the art of Arabic calligraphy is the language and spirit of this Arabism. 5- The Islamic spirit of Arabic calligraphy has breathed into it an aesthetic and aesthetic dimension, making it a symbol of Islamic urbanism and decoration on clothing and others.